Porous synthetic hydrogel carrying basic fibroblast growth factor with controllable and rapid degradation rate to promote wound healing. Issue 6 (November 2022) - Wu, Qian; Gu, Huijie; Cui, Haiyan; Zhou, Shu
Porous hydrogel dressings show breathability and possibility to carry and release basic fibroblast growth factor (bFGF) to promote wound healing. However, the difficult replacement may lead to the secondary damage. Thus, there is an urgent need to develop a method platform to control the degradation rate of hydrogel, so as to realize the on-demand replacement. The present study fabricated a porous hydrogel from co-polymized N, N ′ -bis(acryloyl) cystamine (BAC), allyl polyethylene glycol 500 (APEG500) and acrylic acid (AA) with the presence of polycaprolactone (PCL). BAC contains disulfide bond, which crosslinked the hydrogel. The pore size of the porous hydrogel was 400–600 μm. Higher content of BAC indicated higher crosslinking density, which reduced swelling ratio of hydrogel, while promoted hydrogel storage modulus. At the same time, the presence of PCL reduced swelling ratio of hydrogel, while promoted hydrogel mechanical properties, endowing hydrogel with tough feature. Porous hydrogels that crosslinked by disulfide bonds immersed in glutathione solution were found to degrade spontaneously and quickly due to the response to glutathione. Both crosslinking density and PCL content affected the degradation rate. The porous hydrogel carrying bFGF was applied to wound, promoting angiogenesis, thus accelerating wound healing within 12 d. Due to the spontaneous and rapid degradation of optimized porous hydrogel on wound within 3 days, there was no operation of removing dressing during treatment, avoiding damage during dressing replacement.